(untitled) (The Review of Diabetic Studies, 2025)
Traditional paradigms in the realm of healthcare quality and safety are largely reactive; a notable gap in terms of the relationship between modern health information technologies and quality standards continues to exist; in other words, the latter are not implemented, but rather just co-exist with existing quality standards. In this regard, the current study aimed at alleviating this shortcoming by quantitatively and qualitatively empirically investigating the implications of integrating technology into formal quality procedures on patient outcomes and workflow effectiveness. The cross-sectional, correlational, and mixed-methods design was adopted in three institutions with tertiary care. The sources of data included a survey of 385 healthcare workers, an archival review of 2,147 patient-safety events per 36 months, and a sample of 25 in-depth interview responses. The quantitative analysis sheds light on the existence of a strong positive correlation between Technology-supported Quality Standards (TSQS) and safety culture (r = .681, p =.001) and workflow efficiency (r =.724, p =.001). Most importantly, levels of patient-safety incidence rates showed an overall reduction of 53.8 per cent after implementation because of a decrease from 11.60 to 5.36 per 1,000 patient-days (Chi-square(1) = 264.2, p <.001). Regression diagnostics revealed that TSQS is the most outstanding predictor of efficiency accrual ( = 0.619, p =.001). Qualitatively, lack of training was an identified barrier, especially among the nursing staff. This research concludes that technology is an effective enhancer of quality standards, but its effectiveness is conditional on the strategic implementation that competes with profession-specific preconditions. These results provide a compelling, evidence-based guide on how healthcare executives can maximise technology investments to provide safer, more effective care.